Prove the following trigonometric identities. (secθ + cosθ) (secθ − cosθ) = tan²θ+sin²θ
Answers
Answered by
5
Answer with Step-by-step explanation:
Given : (secθ +cos θ)(sec θ – cos θ) = tan²θ + sin²θ
L.H.S : (sec θ + cos θ)(sec θ – cos θ)
= (sec²θ – cos²θ)
[By using the identity, (a + b)(a – b) = a² – b²]
[By using the identity, sec²θ = 1 + tan²θ and cos²θ = 1 – sin² θ]
= 1 + tan² θ – (1 – sin² θ)
= 1 + tan² θ – 1 + sin² θ
= tan² θ + sin² θ
(secθ +cos θ)(sec θ – cos θ) = tan²θ + sin²θ
L.H.S = R.H.S
Hence Proved..
HOPE THIS ANSWER WILL HELP YOU...
Answered by
10
Answer:
Refer to the attachment mate..☺☺
Attachments:
![](https://hi-static.z-dn.net/files/d62/d1c6e95f45a5f2c512620bb3acf85444.jpg)
Similar questions
Math,
7 months ago
English,
7 months ago
CBSE BOARD X,
1 year ago
English,
1 year ago
Science,
1 year ago